Decision importance as a cue for deferral - Job M. T. Krijnen; Marcel Zeelenberg; Seger M. Breugelmans (Judgment and Decision Making, 2015)
A series of 7 experiments found that people defer important decisions more than unimportant decisions, and that this is independent of choice set composition. This finding persists even when deferral does not provide more flexibility (Experiment 2), when deferral has potential disadvantages (Experiment 3), and when deferral has no material benefits and is financially costly (Experiment 4). The effect of importance on deferral was independent of potential choice conflict (Experiment 5 and 6). The only exception was a situation in which one alternative was clearly dominant; here decision importance did not affect the likelihood of deferral (Experiment 7). These results suggest that people use decision importance as a cue for deferral: more important decisions should take more time and effort.